The Role of Competence and Motivation in Improving Employee Performance - Muhammad Syafri; Marhalinda Marhalinda; Anoesyirwan Moeins (Dinasti International Journal of Education Management And Social Science, 2022)
The South Jakarta City Investment and One-Stop Integrated Services Service as one of the Regional Apparatus Organizations (OPD) of the South Jakarta city government, which has the authority to provide investment licensing services in the region, where it is hoped that permit service activities for the community and the business world can be carried out quickly, easy, transparent and certain in accordance with the provisions of the applicable laws and regulations.The purpose of this study was to determine the effect of competence and work motivation on employee performance, both simultaneously and partially, and to be discussed descriptively. The research method used is descriptive and verification. The unit of analysis in this study were employees of the South Jakarta City Investment and One-Stop Service Office with a sample (n) of 34 employees. The analytical method used is path analysis. The results of this study indicate that competence has a positive and significant influence on employee performance, which means that employee competence determines the optimization of employee performance achievement. Based on the results of the partial competency test, the results show that competency has a positive and significant impact on employee performance. Based on the results of the Partial Test of motivation, it was found that motivation has a positive and significant influence on employee performance. Based on the results of the F (simultaneous) test, motivation and competence simultaneously affect employee performance.